2021
DOI: 10.1111/jan.14868
|View full text |Cite
|
Sign up to set email alerts
|

How and when organization identification promotes safety voice among healthcare professionals

Abstract: Aim The aim of this study is to examine the effect of organizational identification on safety voice behaviour, focusing on the mediating role of safety motivation and the moderating role of management commitment to safety and psychological safety. Design The study used a cross‐sectional questionnaire and a convenience sampling method. Method Data were collected online during November 2019 from 165 staff members from a disability healthcare organization in Australia that employs over 800 staff. Nearly 80% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…Specifically, when nurses perceive greater teamwork within their healthcare teams, they tend to be more satisfied with their jobs, effectively reducing burnout and resulting in reduced turnover intentions. Studies have found that the collaboration, communication, and interaction that take place when working as a team are known to increase nurses' organizational identification and sense of contentment, leading to higher intentions to stay 6,19 ; this underscores the importance of improving teamwork within healthcare teams as an organizational approach to providing holistic nursing care and enhancing nurse retention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, when nurses perceive greater teamwork within their healthcare teams, they tend to be more satisfied with their jobs, effectively reducing burnout and resulting in reduced turnover intentions. Studies have found that the collaboration, communication, and interaction that take place when working as a team are known to increase nurses' organizational identification and sense of contentment, leading to higher intentions to stay 6,19 ; this underscores the importance of improving teamwork within healthcare teams as an organizational approach to providing holistic nursing care and enhancing nurse retention.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have indicated that nurses tend to be committed, highly contented, and significantly more engaged in their work when they perceive their teams to be collaborative 16,18 . In other studies, increased teamwork has been linked to heightened organizational identification and sustained psychological well‐being among nurses 19,20 . Based on this evidence, it is likely that interprofessional teamwork within healthcare teams may reduce turnover intention among nurses by strengthening job satisfaction and reducing burnout 13,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Contextual-level factors are related to the healthcare facility and its organizational culture and administrative policies that support or oppress employee voice: they can be exhibited in the behaviour of the direct supervisor, the fear of retaliation and becoming professionally isolated, lack of action concerning previously raised issues, strict hierarchical communication, etc. (Alingh et al, 2019;Hu & Casey, 2021;Levine et al, 2020;Rich et al, 2019;Stimpfel et al, 2019). The broad system-level factors are formed by the prevailing culture in each country or local context and by the norms that define what is socially acceptable in each situation (Bruyneel et al, 2019;Kritsotakis et al, 2015;Sharp et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The higher organizational identification, the more employees will defend the organization as much as they defend themselves, and act to gain benefits for the organization ( Bradler et al, 2016 ). Research suggested that individuals have many different identities, but individuals strive to seek and maintain positive social identities, and once established, such positive social identities create positive incentives for individual behaviors ( Ng and Feldman, 2013 ; Hu and Casey, 2021 ). It has been shown that in the case of organizational identification, the outside world has a high responsibility and reputation for good deeds, and individuals will more often implement behavioral strategies that match their own identity ( Rosaz et al, 2016 ).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…This paper posits that organizational identification is a perception of an individual’s relationship with an organization and can effectively explain individuals’ differentiated responses when faced with customer bullying ( Akerlof and Kranton, 2000 ). According to COR, organizational identification as a psychological resource can motivate employees to work proactively and positively, thus reducing the generation of negative cognition and behaviors ( Stamper and Masterson, 2002 ; Hu and Casey, 2021 ). Specifically, when individuals regard themselves as insiders in their organization, their sense of resource adequacy is potentially enhanced.…”
Section: Introductionmentioning
confidence: 99%